ANALISIS MOTIVASI SHOLAT PADA SISWA KELAS X IIS 2 SMA NEGERI 1 SUNGAI RAYA - Faaiz Nazzun Lughowiiy; Puwanti Puwanti; Yuline Yuline (Universitas Tanjungpura, 2023)
This research aims to determine the motivation for prayer in class xi iis 2 students at SMA Negeri 1 Sungai Raya. While the specific purpose of this research is to find out the characteristics of students who have low prayer motivation. The impact of low prayer motivation on students. Factors causing low prayer motivation in students. Efforts of guidance and counseling teachers in overcoming low prayer motivation in students. The method used in this study is qualitative and the data collection tools used are interviews and questionnaires. The subjects in this study were 2 students, 2 parents of students, supervising teachers, and 2 peers of students. The results of this research indicate that the characteristics of students who have low prayer motivation are carrying out worship only to avoid scolding from their parents. The impact of low prayer motivation is that students are often negligent in carrying out their obligations. Internal factors that cause low prayer motivation in students are the lack of understanding of the meaning of worship, while external factors are due to the lack of attention of parents in educating children. The guidance and counseling teacher's efforts in overcoming low prayer motivation are by providing information services and following up by establishing related joint work